PERKEMBANGAN RAGAM HIAS TENUN IKAT GEDOG BANDAR KIDUL MOJOROTO KOTA KEDIRI JAWA TIMUR - Tri Atmoko; D. Dharsono (Institut Seni Indonesia Surakarta, 2015)
This research is entitled â€œPerkembangan Ragam Hias Tenun Ikat Gedog Bandar Kidul Mojoroto Kota Kediriâ€(The Development of Ornaments Variety of Tenun Ikat Gedog in Bandar Kidul, Mojoroto, Kediri). It usesdescriptive analysis approach and quantitative data in order to learn how the existence and the developmentof tenun ikat gedog Bandar Kidul Mojoroto, Kediri, is; how the function of the tenun ikat gedog is; how theornaments variety is; and how the aesthetic value in the ornaments variety of tenun ikat gedog Bandar KidulMojoroto, Kediri. The various ornaments and their appearance are analyzed in this research. Unfortunately,tenun ikat Bandar Kidul is not very popular in Kediri especially among the young generation. It happensbecause of many factors, for example, the lack of promotion, there is not enough stock in the market, andthe high price of tenun ikat so that it influences the production. The existence of tenun ikat gedog BandarKidul is one of the cultural works of Indonesian people that has to be maintained in order to preserve thecultural heritage. Aesthetically, the creativity can be found in the beautiful patterns and ornaments variety inthe tenun, while culturally, tenun can be used as a symbol in every ceremony and in every activities of thelocal society in order to preserve Indonesia culture.Keywords: the development of ornaments variety, aesthetics